Penyelesaian Kredit Macet di Bank NTT - Stefanus Don Rade; Firgilius Kandro Mego Asman; Engelbertus Tobu; Allesandro Patricio Quinaldy (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This writing aims to find out the precautionary principle in granting credit to the NTT BANK and find out the efforts made by the NTT BANK in legal settlement in the event of default if the debtor has passed away. This research was carried out at NTT BANK Oebobo Branch. The type of research in the preparation of this thesis is empirical. The population studied is the settlement of bad debts due to default for debtors. Data sources in this study consisted of primary data and secondary data. Data collection techniques were carried out using library research and interviews. The data analysis method used is qualitative. The results of this study are The precautionary principle in extending credit to NTT BANK is when credit applications, credit analysis, credit decisions, credit realization and credit development, while the efforts in legal settlement in the event of default if the debtor has passed away are restructuring, attempts to collect by way of a warning letter or subpoena and auction of mortgage rights through the Office of State Property Services and Auctions. Not all creditors can return credit as promised in the contract. To guarantee the creditor's trust in paying off credit by the debtor, a collateral object is needed. Regarding collateral objects, immovable property is bound with Mortgage Guarantee institutions. But there are often problems in executing collateral objects. Normative legal research that discusses doctrinal law uses the statutory and concept approaches. This study aims to find the most effective way to carry out executions that benefit both parties. Execution of collateral can be done through public auctions or underhanded execution. Execution of Credit Collateral which is burdened with Under Right Handling Rights is one of the alternatives that is considered easier and must take precedence.